2020
DOI: 10.1002/pits.22436
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory voice: Implementation of a district‐led student‐voice program in urban high schools

Abstract: This qualitative case study explores how urban high schools implement a district-initiated student-voice program, referred to as Student Advisory Committees, intended to improve school climate. The study uses an implementation science framework to analyze interview data from principals and advisors in 22 urban high schools. An iterative, top-down thematic analytic procedure was used for analysis and interpretation of the data. The results suggest wide variation in how the program was implemented in terms of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…Degree of Change. Commitment to change ranges from performative to transformative (Biddle, 2019; Biddle & Hufnagel, 2019; Dobson & Dobson, 2021; Giraldo-García et al, 2021; Halliday et al, 2019; Warren & Marciano, 2018). Certainly, some student voice practices may be tokenistic or “just for show,” not actually intended to effectuate change (Biddle & Hufnagel, 2019; Mayes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Degree of Change. Commitment to change ranges from performative to transformative (Biddle, 2019; Biddle & Hufnagel, 2019; Dobson & Dobson, 2021; Giraldo-García et al, 2021; Halliday et al, 2019; Warren & Marciano, 2018). Certainly, some student voice practices may be tokenistic or “just for show,” not actually intended to effectuate change (Biddle & Hufnagel, 2019; Mayes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Giraldo‐García et al . (2021, p. 66) who studied a district's implementation of a student voice project revealed that the authors were “active advocates for student‐voice and of its benefits, which may influence their perception of the implementation.” Newman and Ingraham (2020) discussed how they began their study by valuing a specific model of consultation.…”
Section: Key Findingsmentioning
confidence: 99%
“…Craggs and Kelly (2018, p. 60) disclosed how their research study on students who were moved from regular schools to alternative schools “arose out of experience of direct work with students who have undertaken [such] managed moves.” Giraldo‐García et al . (2021) revealed one of the researchers had been actively involved in the district before the study and thus had preconceived ideas about how programs were implemented there. Vega et al .…”
Section: Key Findingsmentioning
confidence: 99%
See 2 more Smart Citations